A link between PKR, inflammasome and synaptic plasticity:Is it an emerging therapeutic option for cognitive dysfunction? - (:unkn) unknown (TURKISH ASSOC PSYCHOPHARMACOLOGY, 2020)
A cognitive decline biomarker candidate, RNA-dependent protein kinase R (PKR), is proposed to play a crucial role on inflammation, and psychiatric disorders through prolonged metabolic stress, cellular and molecular imbalance by regulating central cellular processes including mRNA translation, transcriptional control, apoptosis, and cell proliferation. PKR is an interferon-induced serine/threonine protein kinase and a well-known master regulator of protein synthesis via phosphorylating the translation initiation factor alpha (eIF2 alpha). Inflammasome assembly consists of large multiprotein complexes that are activated by the pathogen or damage-associated signals resulting in the formation of proinflammatory cytokines such as interleukin-1 beta (IL-1 beta), IL-18, and high-mobility group box 1 (HMGB1) protein. Release of pro-inflammatory cytokines and chemokines triggered by the host's innate immune response against harmful pathogens coordinated by inflammasomes. PKR and inflammasomes have share similar function including innate immunity and defense against viruses. The upstream molecular mechanisms underlying the regulation of inflammasome activation poorly identified. Here, we focused on the role of PKR on the regulation of inflammasome assembly formation by summarizing current investigations that are linked to inflammation/neuroinflammation-driven synaptic plasticity. Virus, inflammatory, and toxic cellular signals activate this protein kinase and then it initiates translation blockade via its downstream target. PKR activation also contributes to inflammation and immune dysfunction through the regulation of inflammatory cell signaling pathways. Cytokines regulated by inflammasomes are critical mediators of psychiatric diseases and neurodegenerative disorders. Previous works have suggested that systemic inflammation could contribute to neuroinflammation and related neurodegeneration via activation of inflammasome assembly. Previous researches found that PKR physically interacted with different inflammasomes. Recent investigations highlighted a key role for PKR in the regulation of inflammasome-mediated diseases and cognitive function. PKR might be a valid target to modulate neuroinflammation and neurodegeneration by modulating inflammasomes. Hence, it is conceivable to hypothesize that PKR could be a pharmacologically alluring objective for treating neuroinflammatory diseases by modulating inflammasome activation in parallel with learning and memory deficits. In the future, the assessment of this kinase levels in blood of patients would enable us to find novel biomarkers to struggle neuroinflammatory process in neurodegenerative and psychiatric diseases.
Keywords: PKR; inflammation; inflammasome; synaptic plasticity